Ultraviolet sterilization and boiling a comparative study - Eleazar, Eufrosina Theodora R.; De Leon, Regina Francine R.; Estaniel, Cynthia (Adviser).
The ultraviolet ray sterilizer for dental instruments was tested as to its efficiency as a method of sterilization in comparison with the more conventional means, boiling. The study was conducted with the use of paper clips as simulated dental instruments. Previously sterilized paper clips were inoculated in stock specimen cultures as S. Aureus, a non-spore former, and B. Subtilis, a spore-former. Paper clips were then subjected to the sterilization methods under study then placed in BHI broth and incubated for 24 hours at 37c. Samples of these were placed in nutrient agar as a suitable medium for colony proliferation after 24 hours of incubation at 37c. The parameter thus used to assess effectivity of boiling and UV radiation for sterilization was the ability of microorganisms to grow even after boiling or UV irradiation. Ten trials show significant results where repeated patterns indicate boiling to be a more effective method than UV sterilization, with isolated cases of exceptional results.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental instruments and apparatus -- Sterilization; Ultraviolet radiation